Relationship between substance abuse and childhood traumas and attachment styles in adults - Seyfeli, Efe Barkın; Şener , Özlem (Journal of Dependence, 2022)
Objective: The aim of this study is to examine the relationship between substance abuse and childhood traumas and attachment styles in adults. Method: The study group consists of 279 participants. In the study, 55 data were collected from patients hospitalized in Balıklı Rum hospital by face to face survey method and 224 data were collected through online survey method and Google Forms. In this study, Demographic Information Form, Alcohol Cigarette and Substance Involvement Screening Test (ASSIST), Chidldhood Trauma Scale (CTS) and Three-Dimensional Attachment Styles Scale (SUBBS) were used. Results: The scores obtained from the physical abuse and anxious attachment subscales predicted the tobacco risk scores. Physical neglect, emotional neglect, sexual harassment subscale, and scores from the CTQ total and scores from the three-dimensional attachment styles subscales predicted alcohol risk scores; scores from physical abuse, physical neglect and overprotection subscales and scores from three-dimensional attachment styles were found to significantly predicted the risk scores of cannabis origin. Conclusion: Adults with substance addiction were generally exposed to trauma in their childhood and that childhood traumas and attachment styles predicted substance addiction.